Rapid and automated risk stratification by determination of the aortic stiffness in healthy subjects and subjects with cardiovascular disease - Lortz, Julia (PLoS One, 2019)
BACKGROUND: Aortic stiffness is an independent predictor of cardiovascular morbidity and mortality; thus, simple, rapid and preferably automated techniques are indispensable for pursuing a global risk stratification approach. We present an oscillometric technique for determination of the carotid-femoral pulse wave velocity (cfPWV), including the diagnostic accuracy, sensitivity and specificity, with emphasis on the training curve and procedural duration. METHODS: In a single-centre crossover study, we evaluated subjects free of known cardiovascular disease (CVD), subjects with CVD and a subgroup of subjects with peripheral artery disease (PAD) in terms of ankle-brachial index (ABI) and PWV measurements determined by oscillometry compared to tonometry. Pearson’s correlation analysis was used to assess the relationship of the PWV measurements determined by both methods. Moreover, the time and cost of the examinations were compared. RESULTS: A total of 176 study subjects underwent assessments to obtain oscillometric and tonometric PWV measurements. The CVD-free subjects (n = 59) were younger (60.4±15.6 vs. 67.5±12.9 years, p = 0.003) than the subjects with CVD (n = 117). The PWV measurements showed significant correlations in CVD-free subjects (r = 0.797, p<0.001), in subjects with CVD (r = 0.817, p<0.001) and in the subgroup of subjects with PAD (r = 0.807, p<0.001). The examination duration was shorter for the oscillometric method than the tonometric method (4.4±0.5 vs. 9.2±0.8 min, p<0.001). CONCLUSION: Using a simple and rapid automated oscillometric method, we achieved good diagnostic accuracy for the determination of aortic stiffness through the PWV in both subjects with and without CVD. This method might be helpful in daily practice in terms of saving time and reducing procedural complexity for screening for cardiovascular morbidities and vascular damage in cases of atherosclerosis.